Caveolin 1 (Cav-1) and actin-related protein 2/3 complex, subunit 1B (ARPC1B) expressions as prognostic indicators for oral squamous cell carcinoma (OSCC) - Auzair, L.M.; Vincent-Chong, V.K.; Ghani, W.M.N.W.A.; Kallarakkal, T.G.; Ramanathan, A.; Lee, C.E.; Rahman, Z.A.A.; Ismail, S.M.; Abraham, M.T.; Zain, R.B. (Springer Verlag (Germany), 2016)
Caveolin-1 (Cav-1) and Actin-Related Protein 2/3 Complex, Subunit 1B (ARPC1B) have been implicated in various human cancers, yet its role in tumorigenesis remains controversial. Therefore, this study aims to determine the protein expression of these two genes in oral squamous cell carcinomas (OSCCs) and to evaluate the clinical and prognostic impact of these genes in OSCC. Protein expressions of these two genes were determined by immunohistochemistry technique. The association between Cav-1 and ARPC1B with clinico-pathological parameters was evaluated by Chi-square test (or Fisher exact test where appropriate). Correlation between the protein expressions of these 2 genes with survival was analyzed using Kaplan–Meier and Cox regression models. Cav-1 and ARPC1B were found to be significantly over-expressed in OSCC compared to normal oral mucosa (p = 0.002 and p = 0.033, respectively). Low level of ARPC1B protein expression showed a significant correlation with lymph node metastasis (LNM) (p = 0.010) and advanced tumor staging (p = 0.003). Kaplan–Meier survival analyses demonstrated that patients with over-expression of Cav-1 protein were associated with poor prognosis (p = 0.030). Adjusted multivariate Cox regression model revealed that over-expression of Cav-1 remained as an independent significant prognostic factor for OSCC (HRR = 2.700, 95 % CI 1.013–7.198, p = 0.047). This study demonstrated that low-expression of ARPC1B is significantly associated with LNM and advanced tumor staging whereas high expression of Cav-1 can be a prognostic indicator for poor prognosis in OSCC patients.